The role of a genetically stable, novel oral type 2 poliovirus vaccine in the poliomyelitis endgame - Sue Ann Costa Clemens; Gustavo Mendes Lima Santos; Isabela Gonzalez; Ralf Clemens (Pan American Health Organization, 2023)
Poliovirus infection causes paralysis in up to 1 in 200 infected persons. The use of safe and effective inactivated poliovirus vaccines and live attenuated oral poliovirus vaccines (OPVs) means that only two pockets of wildtype poliovirus type 1 remain, in Afghanistan and Pakistan. However, OPVs can revert to virulence, causing outbreaks of circulating vaccine-derived poliovirus (cVDPV). During 2020-2022, cVDPV type 2 (cVDPV2) was responsible for 97-99% of poliomyelitis cases, mainly in Africa. Between January and August 2022, cVDPV2 was detected in sewage samples in Israel, the United Kingdom and the United States of America, where a case of acute flaccid paralysis caused by cVDPV2 also occurred. The Pan American Health Organization has warned that Brazil, the Dominican Republic, Haiti and Peru are at very high risk for the reintroduction of poliovirus and an additional eight countries in Latin America are at high risk, following dropping vaccination rates (average 80% coverage in 2022). Sabin type 2 monovalent OPV has been used to control VDPV2 outbreaks, but its use could also lead to outbreaks. To address this issue, a more genetically stable, novel OPV2 (nOPV2) was developed against cVDPV2 and in 2020 was granted World Health Organization Emergency Use Listing. Rolling out a novel vaccine under the Emergency Use Listing in mass settings to contain outbreaks requires unique local regulatory and operational preparedness.